2023
DOI: 10.1039/d2ja00338d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of fluorine in human teeth by cryogenic laser ionization time-of-flight mass spectrometry

Abstract: The scarcity of technology to visualize the fluorine (F) distribution hinders the comprehensive understanding of the role of anti-caries fluorides. In this study, the liquid nitrogen cooling device was introduced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…By observing the spectra in an ICP discharge it was possible to overcome Doppler broadening and resolve the separate lines. Lines of the even Xe isotopes (136,134,132,130,128) were fully resolved for the transitions near 820.860 nm and 841.150 nm. Weak lines of peaks of 124 Xe and 126 Xe with low natural abundances were not observed.…”
Section: Instrumentation Fundamentals and Chemometricsmentioning
confidence: 97%
See 2 more Smart Citations
“…By observing the spectra in an ICP discharge it was possible to overcome Doppler broadening and resolve the separate lines. Lines of the even Xe isotopes (136,134,132,130,128) were fully resolved for the transitions near 820.860 nm and 841.150 nm. Weak lines of peaks of 124 Xe and 126 Xe with low natural abundances were not observed.…”
Section: Instrumentation Fundamentals and Chemometricsmentioning
confidence: 97%
“…Typical reproducibility of d 130 Te/ 125 Te was found to be ± 0.07& (2SD) with samples containing 20 ng mL −1 . If d 130 Te is measured at this level of analytical precision, it was concluded that terrestrial samples were unlikely to have a signicant impact from mass-independent Te isotope effects in meteorites and terrestrial samples. Sn isotopes have not been extensively investigated but She et al 165 analysed cassiterite (SnO 2 ) using LA-MC-ICP-MS.…”
Section: Stable Isotope Ratio Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of fluorine is a challenge with conventional atomic spectrometric techniques, so Ma et al 185 reported an approach employing cryogenic laser ionisation TOF-MS to assess the F content of teeth . The setup used liquid nitrogen to cool the ion source to −25 °C and pressurised the chamber to 300 Pa with He gas.…”
Section: Applications: Clinical and Biological Materialsmentioning
confidence: 99%